2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--18416
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Faculty Adoption of Tablet PCs in Upper Level Engineering Courses

Abstract: The University of Louisville's J.B. Speed School of Engineering began a student Tablet PC initiative four years ago. As a result of this initiative, Speed School of Engineering classrooms now have a one to one Tablet PC deployment. Leveraging this environment to improve the teaching and learning in the classroom is the long-term goal of this and many other Tablet PC programs. Many challenges to achieving this goal exist, including: faculty adoption, infrastructure support, and student competency. Faculty membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Due to the note sharing capabilities of the tablet PC, students reported that their confidence in understanding the course material increased 5 . The tablet PC is often used as a replacement for a whiteboard or overhead projector due to its natural handwriting and annotation capabilities using the stylus 6 .…”
Section: Slate Enabled Technologymentioning
confidence: 99%
“…Due to the note sharing capabilities of the tablet PC, students reported that their confidence in understanding the course material increased 5 . The tablet PC is often used as a replacement for a whiteboard or overhead projector due to its natural handwriting and annotation capabilities using the stylus 6 .…”
Section: Slate Enabled Technologymentioning
confidence: 99%